Association Between Water and Sanitation with Anemia in Preschool Children: Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) Project (P10-087-19). (13th June 2019) - Yu, Emma Xinchun; Williams, Anne; Addo, O Yaw; Suchdev, Parminder; Guo, Junjue; Ismaily, Sanober; Young, Melissa Fox
Abstract: Objectives: We aimed to assess the associations between water source and sanitation with anemia in preschool children (age: 6–59 months) in 16 population-based surveys. Methods: We analyzed data from the BRINDA project. Sixteen surveys, representing 15 countries ( n = 25, 214), that had measures of hemoglobin, household water source and sanitation, type of residence, and socioeconomic (SES) status were included in this analysis. Anemia was defined as altitude-adjusted hemoglobin concentration <110 g/L. Water source and sanitation were defined as improved household drinking water source and improved toilet facility, respectively. Bivariate analyses were done using Rao-Scott chi-square test (except for age, a continuous predictor using logistic regressions). Multivariable logistic regressions were conducted to examine associations between anemia and water source and sanitation, adjusting for age, sex, rural-urban location, and SES. All analyses were conducted with SAS 9.4, accounting for complex survey design. Results: The prevalence of anemia ranged from 20.0% in Nicaragua to 72.1% in Kenya 2010. The prevalence of improved water source and improved sanitation ranged from 44.1% in Laos to 98.4% in Bangladesh, and from 0.1% in Kenya 2007 to 93.7% in Ecuador, respectively. Improved water source alone was protective of anemia in two surveys. Improved sanitation alone was protective of anemia in three surveys. Improved water source alone was negatively associated with anemia in one survey. Improved water source and sanitation combined was protective of anemia in 4 out of 16 surveys, specifically Afghanistan (adjusted OR = 0.55, 95% CI: 0.31–0.96), Azerbaijan (adjusted OR = 0.55, 95% CI: 0.31–0.999), Bangladesh (adjusted OR = 0.03, 95% CI: 0.002–0.28), and Laos (adjusted OR = 0.37, 95% CI: 0.17–0.80). Conclusions: Improved household water source and sanitation was inversely associated with anemia in some settings. However, results were not consistent across surveys, and there may be thresholds at which water source and sanitation impacts anemia. Further research is warranted to evaluate the potential mechanisms that explain links between water source and sanitation with anemia. Funding Sources: Bill & Melinda Gates Foundation.